Reflective stage in teacher education for children education (Olhar de Professor, 2020)
Early childhood education is the first stage of basic education and requires a teaching professional whoacts responsibly. In the search for the formation of the training processes, we proposed the following problem: howto configure a theoretical-practical initial training in the supervised stage of Early Childhood Education, to act inthe pedagogical practice, enabling the production of knowledge? As a general objective, we analyze the theoretical-practical contributions required of professionals who will work in early childhood education, investigating howinitial training can prepare them to work at this level of education, which allows the reception of knowledgeproduction. Methodologically, we involved in the qualitative research the students of the Pedagogy course whoattended the supervised internship for the elaboration of an internship proposal in an investigative perspective. Weconcluded that the professional who will work in early childhood education needs to promote theoretical-practicalarticulation for a meaningful performance. It is necessary to have a conscious look at their transforming role, aswell as the responsibility of this professional to work with children, as being the basis of the subject’s education.
Keywords: Child education. Theory and practice. Supervised internship.